2005
DOI: 10.1177/0886109905277751
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Impact of Domestic Violence Across Age Cohorts

Abstract: This study examined the nature and extent of domestic violence and its impact on psychosocial functioning among women of different age groups. No differences were found across age groups in the severity of violence, nature of injuries, use of alcohol or drugs at the time of the incident, attribution of blame, likelihood to report violence, or rates of childhood physical abuse and depression. However, the older women were more likely to have experienced violence for a longer time, to be in current violent relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 23 publications
5
74
1
1
Order By: Relevance
“…The time courses of Ang-1, Tie2, and VEGF mRNA after exposure to hypoxia were comparable in both methods (data not shown). As the Ang-1/Tie2 system and VEGF signaling pathways play important roles for endothelial function, and endothelial dysfunction has been reported in experimental and human PH, expression of eNOS was also evaluated [1,2,3,4, 11]. mRNA expression of eNOS was significantly upregulated after 0.5–21 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The time courses of Ang-1, Tie2, and VEGF mRNA after exposure to hypoxia were comparable in both methods (data not shown). As the Ang-1/Tie2 system and VEGF signaling pathways play important roles for endothelial function, and endothelial dysfunction has been reported in experimental and human PH, expression of eNOS was also evaluated [1,2,3,4, 11]. mRNA expression of eNOS was significantly upregulated after 0.5–21 days.…”
Section: Resultsmentioning
confidence: 99%
“…As Tie2 and VEGF are known as survival factors of endothelial cells, the decreases in expression might result in apoptosis of vascular cells [1,2,3,4, 11]. Thus we next investigated the expression of caspase-3, which is known as an important effector enzyme for apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This constellation of factors may make older women more difficult to serve in domestic violence programs. Wilke and Vinton's (2005) study examined the nature and extent of IPV and its impact on psychosocial functioning among women of different age groups. Findings confirmed that older women experience just as much IPV as younger women, but had more needs than younger women.…”
Section: Culturally Competent Interventions For Elder Intimate Partnementioning
confidence: 99%
“…While the disproportionate risk of young women (e.g., of childbearing age), particularly those who are pregnant, is well documented [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], a growing empirical literature also characterizes the significant prevalence and public health implications of interpersonal abuse exposure, including verbal, physical or sexual abuse, neglect, and financial exploitation, among older, post-menopausal women [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. For example, Zink et al [33] conducted a telephone survey investigating prevalence of abuse exposure among more than 3500 women over age 55.…”
Section: Introductionmentioning
confidence: 99%